Lactate dynamics in paediatric patients with severe sepsis: insights from a prospective cohort study - Tarek A. Abdelaziz; Nehad Ahmed Karam; Weaam Ibrahim Ismail; Nahed Mohamed Ali Askary; Eman Gamal Baz (BMC, 2024)
Abstract Background Sepsis is an infection-related systemic inflammatory response that often leads to elevated lactate levels. Monitoring lactate levels during severe sepsis is vital for influencing clinical outcomes. The aim of this study was to assess the association between plasma lactate levels and mortality in children with severe sepsis or septic shock. Methods The current prospective study was conducted in the PICU of University Children's Hospital. The International Paediatric Sepsis Consensus Conference criteria for Definitions of Sepsis and Organ Failure in 2005 were used to diagnose patients with sepsis. We measured plasma lactate levels upon admission (Lac H0) and 6 h later (Lac H6). The static indices included the absolute lactate values (Lac H0 and Lac H6), while the dynamic indices included the delta-lactate level (ΔLac) and the 6-hour lactate clearance. The 6-hour lactate clearance was calculated using the following formula: [(Lac H0-Lac H6)100/Lac H0]. ΔLac was calculated as the difference between the Lac H0 and Lac H6 levels. Patient survival or death after a PICU stay was the primary outcome. Results A total of 46 patients were included in this study: 25 had septic shock, and 21 had severe sepsis. The mortality rate was 54.3%. The Lac H0 did not significantly differ between survivors and nonsurvivors. In contrast, the survivors had significantly lower Lac H6 levels, higher ΔLac levels, and higher 6-hour lactate clearance rates than nonsurvivors. Lactate clearance rates below 10%, 20%, and 30% were significantly associated with mortality. The best cut-off values for the lactate clearance rate and Lac H6 for the prediction of mortality in the PICU were < 10% and ≥ 4 mmol/L, respectively. Patients with higher Lac H6 levels and lower lactate clearance rates had significantly higher PICU mortality based on Kaplan-Meier survival curve analysis. Conclusions This study highlights the significance of lactate level trends over time for the prediction of mortality in the PICU in patients with severe sepsis or septic shock. Elevated lactate levels and decreased lactate clearance six hours after hospitalisation are associated with a higher mortality rate.